Doing 'Upstream' Priority-Setting for Global Health with Justice: Moving from Vision to Practice?. (3rd June 2016) - Syrett, Keith
Abstract: The vision of global health with justice which Larry Gostin articulates in his book Global Health Law envisages a switch to 'upstream' priority-setting for expenditure on health, with a focus upon social determinants and a goal of redressing health inequalities. This article explores what is meant by this proposal and offers a critical evaluation of it. It is argued that difficulties arise in respect of the ethical and evidential bases for such an approach to the setting of priorities, while significant challenges may also arise in the necessary modification of structures of governance.